2017
DOI: 10.3847/2041-8213/835/2/l19
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Subarcsecond Bright Dots in the Transition Region above Sunspots and Their Relation to Penumbral Micro-jets

Abstract: Recent high-resolution observations reveal that subarcsecond bright dots (BDs) with sub-minute lifetimes appears ubiquitously in the transition region (TR) above sunspot penumbra. The presence of penumbral microjets (PMJs) in the chromosphere have also been reported earlier. It was proposed that both the PMJs and BDs are formed due to magnetic reconnection process and may play an important role in heating of the penumbra. Using simultaneous observation of the chromosphere from the Solar Optical Telescope (SOT)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 24 publications
2
31
0
Order By: Relevance
“…8 agrees with the results presented by Reardon et al (2013), in particular, with those provided by Samanta et al (2017). The assertion by Samanta et al (2017) that PMJs host a preceding brightening phase seen in the upper chromosphere and transition region is confirmed by our results. However, the conclusion drawn by Samanta et al (2017) that PMJs are triggered by a reconnection event in the transition region is not supported by our results.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…8 agrees with the results presented by Reardon et al (2013), in particular, with those provided by Samanta et al (2017). The assertion by Samanta et al (2017) that PMJs host a preceding brightening phase seen in the upper chromosphere and transition region is confirmed by our results. However, the conclusion drawn by Samanta et al (2017) that PMJs are triggered by a reconnection event in the transition region is not supported by our results.…”
Section: Discussionsupporting
confidence: 92%
“…The gradual brightening phase illustrated in Fig. 8 agrees with the results presented by Reardon et al (2013), in particular, with those provided by Samanta et al (2017). The assertion by Samanta et al (2017) that PMJs host a preceding brightening phase seen in the upper chromosphere and transition region is confirmed by our results.…”
Section: Discussionsupporting
confidence: 91%
“…They have a progressively weaker signal in lower atmosphere layers, with most events having no signature in Hα . Tian et al (2014a) suggested that bright dots have a connection to the Ca II penumbral microjets which was largely confirmed by , but Samanta et al (2017) identified a distinct class of bright dots without Ca II signature. Penumbral bright dots were also found in 193 Å images from the Hi-C rocket flight ), which were not considered to be coronal features but contributed by cooler TR emission lines in the 193 Å passband.…”
Section: Penumbral Microjets and Sunspot Dotsmentioning
confidence: 90%
“…Simultaneous observations in the chromosphere and TR (Vissers et al 2015;Samanta et al 2017) show that some of these TR bright dots rest at the tips of chromospheric penumbral micro-jets (Katsukawa et al 2007;Tiwari et al 2016). Vissers et al (2015) suggested that these TR bright dots are the heating signature of the penumbral micro-jets, whereas Samanta et al (2017) showed that the majority of the TR dots originate before the generation of the chromospheric jets. These observations left us with an unclear and confused understanding about their origination process and indicated the further need for high-quality imaging and spectroscopic observations.…”
Section: Dynamics In the Tr Above Sunspotsmentioning
confidence: 99%
“…These observations left us with an unclear and confused understanding about their origination process and indicated the further need for high-quality imaging and spectroscopic observations. Interestingly, many bright dots show no detectable signatures in chromospheric images, which might be caused by cooling downflows from the overlying corona (Deng et al 2016, Samanta et al 2017. Another category of small-scale brightenings observed with IRIS is narrow-line-width UV bursts (Hou et al 2016).…”
Section: Dynamics In the Tr Above Sunspotsmentioning
confidence: 99%